Promosi Kesehatan Tentang Upaya Peningkatan Perilaku Hidup Bersih Melalui Nonton Bareng Dan Pemasangan Stiker Dengan Tema Dermatitis di Kelurahan Batu Urip Lubuklinggau Utara II - Cahyawati, Untari; Pamungkas, M HIdayat Ari; Isabella, Isabella; Ayuwandira, Deva; Lestari, Wahyu Heni; Rohani, Tuti (Utami Publisher, 2024)
Personal hygiene is an individual's or group's efforts to maintain health through individual cleanliness by controlling environmental conditions. Clean and Healthy Living Behavior Development (PHBS) aims to build and preserve community behavior that focuses on cleanliness and health, so that people can be independent in preventing and dealing with their own health problems. The aim is to increase public knowledge about the causes of dermatitis. Based on the results of interviews with the people of Batu Urip sub-district, the problem is the low level of public knowledge about the causes of dermatitis. The method used in this activity is an action research method and a participatory activity program with the community through watching together the dangers of bathing in the river and sticking stickers in residents' homes with the theme dermatitis. The result of this activity is that public knowledge about Clean and Healthy Lifestyles (PHBS) free of dermatitis has increased. Knowledge of recognizing the causes of dermatitis is believed to be one of the most important factors in improving the prevention of dermatitis. To increase this knowledge, it is necessary to provide information regarding the causes of dermatitis in the community so that the people of Batu Urip sub-district can understand the importance of maintaining bathing habits and personal hygiene.sticking stickers to increase public knowledge about the causes of dermatitis.